Envisaging Beyond Community-Based Health Insurance in Nepal - Magar, A (Journal of Nepal Health Research Council, 2014)
Every nation in the world, wish to provide all health care free of cost to its citizens, if not easily accessible and more affordable. But all of them have limited resources in terms of infrastructure, health workforce and most importantly the financing. The health financing is one of the six building blocks of a health system, which play crucial role for improving health of a country.